KAJIAN TERHADAP SIKAP GURU DAN PERILAKU SISWA PADA MATA PELAJARAN BIOLOGI BERDASARKAN GENDER DI SMP NEGERI 1 DAN SMP NEGERI 6 BANDA ACEH - Hamama, Syarifah Farissi (Jurnal Edukasi dan Sains Biologi, 2016)
This article report students’ perception on their teacher interpersonal behaviour and their attitude toward Biology  based on gender in two Lower Secondary Schools (SMP Negeri 1 and  SMP Negeri 6) in Banda Aceh. The data were collected using two questionnaires, there are, the Indonesian version of The Teacher Interaction (QTI) and Test of Biology Related Attitude (TOBRA). This study has been done from May to November 2015. A total sample of 243 Students in grade 8 and 9, responded to the questionnaires. The sample was chosen based on Krejcie-Morgan table. This result found that the questionnaires are valid and reliable. There are are no significant differences between male and female perception on teacher interpersonal behaviour, except on Students Responsibility and Admonishing. This study also confirmed that relationship between student perception on teacher interpersonal behaviour and their attitude toward biology is not occurred. Student enjoyment is not related to all scale, except on Strict. Based on regression analysis, it was found that the attitude of the teacher in QTI scales can not be used to predict the students' attitude toward Biology. Keyword:  Teacher behaviour, Student perceptions, Biology, Gender, QTI, TOBRA